1998
DOI: 10.1002/(sici)1521-4125(199802)21:2<187::aid-ceat187>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Organic Pollutants by the Photo-Fenton-Process

Abstract: The Photo-Fenton-Process utilizing the combinations Fe(II)/H 2 O 2 /UVA and Fe(III) oxalate/H 2 O 2 /UVA was employed with success to degrade biorefractory organic pollutants in landfill leachate. The rate of degradation of the organic pollutants depends on the concentrations of hydrogen peroxide and the iron catalyst, the pH value and the concentration of dissolved oxygen. A comparison of the Photo-Fenton-Process with the H 2 O 2 /Fe(II) process and the H 2 O 2 /UVC process shows that the Photo-Fenton-Process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(51 citation statements)
references
References 14 publications
1
49
0
1
Order By: Relevance
“…The net result is that, in the presence of oxalate, the photo-Fenton reaction is intrinsically more efficient, can be induced by a wider range of wavelengths of light, and results in the mineralization of the oxalate ion. Thus, for example, in a municipal water treatment system, Kim & Vogelpohl (1998) found that, with UV irradiation, the photo-Fenton process was at least 30% more energy efficient in the presence of oxalate than in its absence. Clearly, the sensitivity of the ferrioxalate-catalyzed photo-Fenton process to both UV and visible light makes it particularly attractive for applications in which the sun is employed as the radiation source (Silva et al, 2010;Trovó & Nogueira, 2011 (Machulek et al, 2009b).…”
Section: Catalysis Of the Photo-fenton Reaction By Complexation Of Fementioning
confidence: 99%
See 1 more Smart Citation
“…The net result is that, in the presence of oxalate, the photo-Fenton reaction is intrinsically more efficient, can be induced by a wider range of wavelengths of light, and results in the mineralization of the oxalate ion. Thus, for example, in a municipal water treatment system, Kim & Vogelpohl (1998) found that, with UV irradiation, the photo-Fenton process was at least 30% more energy efficient in the presence of oxalate than in its absence. Clearly, the sensitivity of the ferrioxalate-catalyzed photo-Fenton process to both UV and visible light makes it particularly attractive for applications in which the sun is employed as the radiation source (Silva et al, 2010;Trovó & Nogueira, 2011 (Machulek et al, 2009b).…”
Section: Catalysis Of the Photo-fenton Reaction By Complexation Of Fementioning
confidence: 99%
“…types of AOPs that have been proposed in the literature include (oxidant [catalyst, when present]/light): H 2 O 2 /UV (Gryglik et al, 2010;Ho & Bolton, 1998); O 3 /UV (Esplugas et al, 1994;Machulek et al, 2009a); O 3 -H 2 O 2 /UV (Yue, 1993); [TiO 2 ]/UV (Gaya & Abdullah, 2008;Henderson, 2011;Jenks, 2005;Matthews, 1992); Fe(III)/[TiO 2 ]/UV-Vis (Domínguez et al, 1998); direct photolysis of water with vacuum UV (Gonzalez et al, 2004); Fenton reaction or H 2 O 2 -Fe(II) (Dao & Laat, 2011;Haddou et al, 2010;Kwon et al, 1999;Pignatello et al, 2006;Pontes et al, 2010); and the photo-Fenton reaction or H 2 O 2 [Fe(II)/Fe(III)]/UV (Benitez et al, 2011;Kim & Vogelpohl, 1998;Kiwi et al, 1994;Machulek et al, 2007;Martyanov et al, 1997;Nichela et al, 2010;Pignatello et al, 2006;Ruppert et al, 1993). In most AOP, the objective is to use systems that produce the hydroxyl radical, HO…”
Section: Introductionmentioning
confidence: 99%
“…Radiation at 290-400 nm enhances Fenton-like reactions by reduction of Fe III (OH) 2þ to Fe II and the concomitant generation of free OH radicals in this light-induced Fenton or photo-Fenton reaction (Eqn 21). [94] FeðOHÞ 2þ þ hn ! Fe 2þ þ HO ð21Þ…”
Section: Relevant Oxidation Reactionsmentioning
confidence: 86%
“…The use of UV light in combination with Fenton's reagent, that is, the so-called photoFenton process, is able to re-generate ferrous iron reducing ferric ions and producing additional hydroxyl radical content by photolysis according to the following equation (Faust and Hoigne 1990;Kavitha and Palanivelu 2004;Kim and Vogelpohl 1998):…”
Section: Photo-fentonmentioning
confidence: 99%